Critical success factors of the medium-sized independent hotels in Phuket / Rawipaaun Wichayanurak - Rawipaaun Wichayanurak (Prince of Songkla University, 2018)
Thesis (M.B.A., (Hospitality and Tourism Management))--Prince of Songkla University, 2015